Rapid graphitization of a pulsed laser remelted ductile cast iron during multipass overlap melting - Wang, Huaming; Bergmann, Hans Wilhelm (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 1995)
As-cast ductile cast iron with an as-machined shiny metal surface was remelted with a high-power (1 kW) pulsed Nd:YAG laser using both single- and multipass overlap melt tracks. Changes in the microstructure of the underlying laser melted track caused by the transient overlap heating during multipass overlap remelting process were studied. The rapidly solidified metastable ledeburite structure of the underlying laser melted track was found to be rapidly graphitized during overlap remelting. The graphitized zone consists of a fully graphitized zone containing extremely fine graphite nodules and a partially graphitized zone containing extremely fine graphite nodules and undissolved cementite. The overlap ratios of the melt tracks were shown to have no noticeable influence on either the graphitized microstructure and the size of the graphitization zones. This newly observed rapid graphitization phenomenon is preliminarily discussed in terms of the microstructural characteristics of the rapidly solidified ductile iron and the unique heating behavior of pulsed laser beam to material.